Análisis de la sostenibilidad financiera de los Establecimientos Públicos del Departamento de Antioquia y del Distrito Especial de Medellín entre 2021 – 2022, casos Instituto Departamental de Deportes de Antioquia – INDEPORTES Antioquia e Instituto de Deportes y Recreación de Medellín - INDER Medellín - Armenta Daza, Armando Rafael; López Arboleda, Ramiro (Universidad Antonio Nariño, 2023)
This investigation seeks to determine if the public establishments INDEPORTES Antioquia and INDER Medellín are financially self-sustaining, in order to identify strengths and weaknesses in their financial management, which allow establishing if these entities present sources of resources to develop their missionary objective in the short, medium and long term, in a financial environment without major uncertainties.